Biodiesel no Estado da Bahia: potencialidades, entraves e ações indutoras - Silva, Marcelo Santana (2008)
The shortage of oil, the national energy security, global warming and the rising of food prices and consumption are current problems in mankind. Issues related to alternative energy sources are gaining great importance and prominence in political and economic scenario. At a time when biofuels are internationally in evidence, it is essential to debate on this new market. The biodiesel production in Brazil is an example of this reality. Duo to the way the program is being implemented, with around 60% of small plants, and the presence of large oligopolistic industries that dominate the biodiesel business, through auctions, and a huge idle capacity, the current production of oleaginosas is insufficient to supply the industries demand of these plants. The state of Bahia is a typical example of this contrast. In such big programs, at the initial stage, you have many problems that must be discussed and solved. Thus, this work aims to: analyze the potential of several raw materials for the production of biodiesel, those from Bahia in particular; assess the regulatory framework of the Brazilian Biodiesel and the public policies for its promotion in Bahia; and diagnose the main regulatory and agro-economic barriers, suggesting actions to the promotion of biodiesel in the country and in the state of Bahia. The methodology is based on the bibliographic documental search and interviews with the individuals involved in this field. The research showed that Bahia presents difficulties and low conditions to produce and sell biodiesel through its raw materials, to meet its installed capacity, duo to the lack of integration among public policies for the sector in Bahia, the fragility of regulatory framework to promote social inclusion in the North, Northeast and Semi-arid (the taxation, the auctions for the purchase of biodiesel and the Social Fuel Stamp), besides other several investigated barriers. In this sense, this work suggested a Production Organization Pattern through the creation of Biodiesel Production Zones (ZPB) in Bahia